Evaluation of time-dependent pathways in an acute ischemic stroke protocol that incorporates CT perfusion: A tertiary referral center experience - hashim, hilwati; Hassan, Radhiana; Sharis Osman, Syazarina; Muda, Ahmad Sobri (Neurology Asia, 2013)
Background and Objective: Intravenous thrombolysis service for stroke was introduced at the Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in 2009, based on the recommendations of a multidisciplinary team of clinicians. We report the experience at our center in establishing a stroke protocol incorporating computed tomography perfusion (CTP) of the brain, to assess the feasibility of incorporating CTP in the stroke protocol. Methods: A retrospective review of all patients who had a CTP between January 2010 and December 2011 was performed. Results: Of 272 patients who were admitted with acute ischemic stroke, 44 (16.2%) arrived within 4.5 hours from symptom onset and had a CTP performed with the intention to treat. The median time for symptom-to-door, symptom-to-scan and door-to-scan was 90.0 minutes (62.5 – 146.3), 211.0 minutes (165.5 – 273.5) and 85.0 minutes (48.0 – 144.8) respectively. Eight patients (2.9%) were thrombolysed of whom five received IV thrombolysis and three underwent mechanical thrombolysis. The median symptom-to-needle and door-to-needle times were 290.5 minutes (261.3 – 405.0) and 225.0 minutes (172.5 – 316.8) respectively. Four patients were thrombolysed despite being outside the window of treatment based on the CTP findings. Six of the thrombolysed patients had a Modified Rankin Score (MRS) of 1-2 at 5 months post procedure. Conclusions: CTP provides a benefit to management decisions and subsequent patient outcome. It is feasible to incorporate CTP as a standard imaging modality in a stroke protocol. The delays in the time-dependent pathways are due to our work flow and organisational process rather than performing the CTP per se.